The nursing consultation to the carriers of hypertension: the practice - Costa, Francisca Bertilia Chaves; Araújo, Thelma Leite de (Rev Rene, 2008)
The aim of this study was to investigate, in a specific group formed by nurses belonging to the teams of the Family Health Program of Ceará, the practice of the nursing consultation to the people with arterial hypertension. This study was characterized as exploratory-descriptive, developed from 2004 to 2005 with 17 nursing consultations professional promoters to assist the mentioned patients. Some topics inserted in the stages of the nursing consultation were described by the participants of the study. They were related to the complaints identification, physical examinations, and (orientations). However, the consultation of the majority of the participants, are not according with the objectives of the arterial hypertension control on the basis of the Plan of Hypertension and Diabetes Mellitus (2001) attention Reorganization and to the 5th Brazilian Policies for de Arterial Hypertension. According to what was concluded, the professionals approached, incorporate the knowledge on nursing consultation only partially and this still continues much centered, in the traditional biomedical model.